Fenomena Islamofobia di Media Sosial: Tantangan Dan Peluang Dakwah di Masa Mendatang - Syahrul Rahman (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This article aims to present the phenomenon of the islamophobic movement which has become increasingly widespread after WTC and Pentagon explosions in United States. Various accusations have always been addressed to Islam and its followers. Islamophobia is developed systematically and measurably. With the help of social media, Islamophobia is easily spread to all corners of the world, even the effects of Islamophobia are also being felt in a country where the majority of Muslims. Islamophobic actions that occur in the real world will be re-expressed on social media, but very rarely the expression of Islamophobia that occurs on social media, is presented directly in the real world. Islamophobia does not only present disharmony between followers of different religions, but also counterproductive in the life of the nation and state. This research uses descriptive analysis method by researching the previous literature contained in various scientific journals. The result of this article are the recommendations for religious leaders (Muslim scholars) to be actively involved in social media to voice Islam, a friendly religion for all beside in addition to making it easier to counter the presence of Islamophobia in the country